PENGARUH SIKAP GURU TERHADAP MOTIVASI BELAJAR SISWA DI SMA NEGERI 2 TUALANG KABUPATEN SIAK - Depi Syuriani; Hambali Hambali; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstact: This research is motivated by the attitude of the teacher and student motivation of SMA Negeri 2 Tualang Siak District. The formulation of the problem in this study is how the influence of teacher attitudes on student learning motivation SMA Negeri 2 Tualang Siak District. The research objective was to determine how the influence of teacher attitudes on student learning motivation of SMA Negeri 2 Tualang Siak District. The benefits of this research are theoretical benefits, namely this research is expected to provide additional information, especially for teachers, about the relationship between teacher attitudes towards student motivation in learning. The practical benefit is as a basis and reference for further studies related to teacher attitudes and student learning motivation at school to become material for further study. The sample in this study were students of SMA Negeri 2 Tualang Siak District which amounted to 66 respondents determined by purposive sampling technique. The data collection instruments were observation, questionnaire, documentation, and interviews. Processing data with quantitative descriptive analysis using simple linear regression formula assisted by SPSS version 16 application by stating hypotheses; There is an influence between teacher attitudes on student learning motivation of SMA Negeri 2 Tualang Siak District. Based on the results of research on the effect of teacher attitudes on student learning motivation of SMA Negeri 2 Tualang Siak District There is a significant influence between teacher attitudes on student learning motivation of SMA Negeri 2 Tualang Siak District by 45.4%.Key Words: Influence, Teacher Attitudes, Student Motivation